Śrī Śrāddhavidhi prakaraṇa : mūḷa, saṃskrta chāyā, ane tenī svopajña ʻŚrāddhavidhi-kaumudīʼ nāmaka ṭikāno Gurjara anuvāda - Ratnaśekharasūri, 14th cent (Haripharma Korporesana ; prapti sthana, Somacanda Di. Saha, 1978)
Medieval Prakrit verse work, with a Gujarati translation of autocommentary, on Jain conduct of life.